Soft Robots: Implementation, Modeling, and Methods of control - Shahad AbdulAdheem Al-Ibadi; Loai Ali Talib Al Abeach; Mohammed Abd Ali Al-Ibadi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2023)
Soft robotics is a branch of robotics that focuses on technologies with physical features that are like those of live biological creatures. Additionally, they have many details that are hard, if not impossible, to realize with traditional robots which are composed of solid materials. This study concentrates on the current expansion of soft pneumatic actuators for modern soft robotics in recent years, with an emphasis on three areas: Implementation of soft robots, Modeling, and Methods of control systems. Therefore, numerous soft robotic designs and ways to make them suitable for medical, manufacturing, and agricultural applications have been presented. Moreover, a set of functional and technological aspects have been given to review models similar to human hand functionality and motions. To realize the advanced soft robotic hand manipulation function, robotic hands must be equipped with tactile sensing, that sensing is required to provide continuous data on the volume and direction of forces at all contact locations. The research examines achievements in material science, actuation, sensing techniques, and manufacturing technologies, as well as how to model and control a soft robot's motion, all of which are scientifically challenging and, more importantly, practical.